TEMPORAL CHANGES IN DIVERSITY AND SIMILARITY OF BIRD COMMUNITIES OF THREE FOREST FRAGMENTS IN AN URBAN ENVIRONMENT IN PENINSULAR MALAYSIA - Ramli, Rosli (Malaysian Journal of Science, 2004)
A study of changes on diversity and similarity of birds inhabiting three forest fragments around Kuala Lumpur, Malaysia was conducted in two sessions, 1991/1992 and 2000/2001. The study areas were Boldt Gasing Forest Reserve (BGF), Taman Seputih Forest (TSF), and a patch of green area next to First Residential College, Universiti Malaya campus (UMF). Birds were recorded either through direct observation or captured by mist-net. Five diversity indices (i.e. Shannon-Weiner, Simpson, Sorensen, Coefficient Community, and Equitability) were used to determine bird diversity and evenness. In total, 2457 birds comprising 73 species were recorded in the areas. Most of the birds were resident (78%), followed by migratory (11%), uncertain (7%), and introduced species (4%). The highest diversity value was in the BGF and the least was in the UMF. These two sites also shared more similar species than other areas; probably due to their closeness and similarity in forest structure. Results from this study clearly indicate that size and habitat complexity were two main factors that regulated distribution and composition of birds in the study areas